Propose a new Firefly-Fast Learning Network model based Intrusion-Detection System - Mohammed Falih, Badran; Kohbalan, Moorthy; Nor Saradatul Akmar, Zulkifli; Mohd Saberi, Mohamad; Safaai, Deris; Nan, Md. Sahar (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Currently, effective Intrusion-detection systems (IDS) still represent one of the important security tools. However, hybrid models based on the IDS achieve better results compared with intrusion detection based on a single algorithm. But even so, the hybrid models based on traditional algorithms still face different limitations. This work is focused on providing two main goals; firstly, analysis based on the main methods and limitations of the most-recent hybrid model-based on intrusion detection, secondly, to propose a novel hybrid IDS model called FA-FLN based on the Firefly algorithm and Fast Learning Network.